1991
DOI: 10.1002/1097-0142(19910815)68:4<706::aid-cncr2820680407>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy, surgery, and postoperative radiation therapy for invasive thymoma

Abstract: Between January 1988 and June 1990, seven previously untreated patients with histologically confirmed and clinically staged IIIa invasive thymoma (IT) were enrolled in a prospective, single treatment arm study of neoadjuvant chemotherapy (NC) followed by surgery and postoperative radiation therapy (4600 to 6000 cGy). The NC included three cycles of cisplatin (75 mg/m2 on day 1), epirubicin (100 mg/m2 on day 1), and etoposide (120 mg/m2 on days 1, 3, and 5), every 3 weeks. All patients showed a partial response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
2
4

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(82 citation statements)
references
References 27 publications
4
70
2
4
Order By: Relevance
“…Cisplatin based regimens have also proved to be effective in the treatment [3,9,13,14]. In cases similar to ours, neoadjuvant chemotherapy was proposed to improve the respectability of the mass [17,23]. The average survival time of thymic carcinomas in adult series was about 2.5 years [3,9,13,14].…”
Section: Discussionsupporting
confidence: 63%
“…Cisplatin based regimens have also proved to be effective in the treatment [3,9,13,14]. In cases similar to ours, neoadjuvant chemotherapy was proposed to improve the respectability of the mass [17,23]. The average survival time of thymic carcinomas in adult series was about 2.5 years [3,9,13,14].…”
Section: Discussionsupporting
confidence: 63%
“…It has been shown that certain chemotherapy regimens can sterilize thymoma. In a study reported by Macchiarini and colleagues, seven patients with clinically stage III invasive thymoma were given neoadjuvant cisplatin, epirubicin, and etoposide [50]. All seven patients subsequently underwent surgical resection-four complete and three incomplete.…”
Section: Multimodality Therapymentioning
confidence: 99%
“…Several chemotherapy regimens have been used in this setting, mostly consisting of adriamycin-and/or platin-based multi-agent combinations (table 4, fig. 2) [78][79][80][81][82][83][84][85][86][87][88]. Usually two to four cycles of chemotherapy are administered before imaging reassessment.…”
Section: Chemotherapy Principlesmentioning
confidence: 99%